Prognostic Values of Radiosensitivity Genes and CD19 Status in Gastric Cancer: A Retrospective Study Using TCGA Database - Liang LB; Huang XY; He H; Liu JY (Dove Medical Press, 2020)
Libo Liang,1,* Xinyan Huang,2,* He He,3 Ji-Yan Liu4 1Department of International Medical Centre, West China Hospital, Sichuan University, Chengdu 610041, Sichuan Province, People’s Republic of China; 2West China School of Stomatology, Sichuan University, Chengdu 610041, Sichuan Province, People’s Republic of China; 3Department of Laboratory Medicine, West China Hospital, Sichuan University, Chengdu 610041, Sichuan Province, People’s Republic of China; 4Department of Biotherapy, West China Hospital, Sichuan University, Chengdu 610041, Sichuan Province, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ji-Yan Liu Email liujiyan1972@163.comBackground: The correlation between the radiosensitivity genes combined with CD19 status and clinical outcome was investigated to identify gastric cancer (GC) patients who would benefit from radiotherapy combined with CAR-T cell therapy.Methods: The gene expression and clinical features were downloaded from The Cancer Genome Atlas (TCGA) Stomach Cancer (STAD). To identify the hub radiosensitivity genes and CD19 status, 407 patients were categorized into two groups: radiosensitivity (RS) and radioresistance (RR) based on the prognosis. The chi-square test, Mann–Whitney test, and Kaplan–Meier survival analysis were applied to compare the differential expression in these groups and analyze the correlation between the gene expression and clinical outcome and features. Finally, the influencing factors for the prognosis of GC were investigated by multiple Cox regression, especially in RS patients.Results: A total of 15 differential expression genes, containing two communities with 8 hub radiosensitivity genes, were identified. We also identified a 2-gene signature model with a negative coefficient and calculated the risk score for the prognosis of GC. Also, Helicobacter pylori infection was validated, and the high-risk score of radiosensitivity genes was the risk factor, and high CD19 expression was the protective factor for the prognosis.Conclusion: The radiosensitivity gene signature and CD19 expression predicted the clinical outcome of GC patients.Keywords: gastric cancer, radiosensitivity genes, CAR-T cell therapy, TCGA database